2003
DOI: 10.1016/s0006-3495(03)74948-0
|View full text |Cite
|
Sign up to set email alerts
|

A Prestressed Cable Network Model of the Adherent Cell Cytoskeleton

Abstract: A prestressed cable network is used to model the deformability of the adherent cell actin cytoskeleton. The overall and microstructural model geometries and cable mechanical properties were assigned values based on observations from living cells and mechanical measurements on isolated actin filaments, respectively. The models were deformed to mimic cell poking (CP), magnetic twisting cytometry (MTC) and magnetic bead microrheometry (MBM) measurements on living adherent cells. The models qualitatively and quant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
80
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(82 citation statements)
references
References 39 publications
2
80
0
Order By: Relevance
“…Thus, as predicted by the tensegrity model, continuous transmission of tension between different cytoskeletal filament systems, and from the cytoskeleton to both the nucleus and ECM receptors, is critical for cell shape stability. Interestingly, even the submembranous cytoskeleton (the cortical actin-ankyrin-spectrin lattice) appears to require tensional prestress for its mechanical stability (Discher et al, 1998;Coughlin and Stamenovic, 2003).…”
Section: Prestress Is a Major Determinant Of Cell Mechanicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, as predicted by the tensegrity model, continuous transmission of tension between different cytoskeletal filament systems, and from the cytoskeleton to both the nucleus and ECM receptors, is critical for cell shape stability. Interestingly, even the submembranous cytoskeleton (the cortical actin-ankyrin-spectrin lattice) appears to require tensional prestress for its mechanical stability (Discher et al, 1998;Coughlin and Stamenovic, 2003).…”
Section: Prestress Is a Major Determinant Of Cell Mechanicsmentioning
confidence: 99%
“…they lack internal compression struts) can mimic the cell's response to generalized membrane deformation (e.g. owing to poking of a cell with an uncoated micropipette), they cannot explain many other cell mechanical behaviors, especially those that are measured through cell-surface receptors that link to the internal cytoskeleton (Coughlin and Stamenovic, 2003).…”
Section: Mathematical Formulation Of the Tensegrity Theorymentioning
confidence: 99%
“…Experiments, however, have shown that the strain field is far from homogeneous, is widely distributed throughout the cell, and tends to be focused at regions around focal adhesions, so there are clearly additional structural features that need to be incorporated into the models. One aspect, the discrete nature of the force-transmitting filaments, is included in the theoretical analyses of tensegrity structures (17). Other factors associated, for example, with the localized attachment of the cell via focal adhesions also need to be considered in all these models.…”
Section: Force Transduction Pathways and Signalingmentioning
confidence: 99%
“…Material properties have been estimated for cell constituents such as cytoskeletal proteins, cytoskeletal networks, lipid bilayers, and plasma membranes, as well as whole cells including alveolar and bronchial epithelial cells (113,114). In the context of a discussion on cell injury two characteristics of biomaterials deserve comment: (1 ) the distinct rheologic properties of network structures (115)(116)(117) and (2 ) the importance of active remodeling in determining cell plasticity (118)(119)(120).…”
Section: Microrheology Of Living Cellsmentioning
confidence: 99%